Lagged Association Rate (LAR) of humpback whales in the Kitimat Fjord System, parsed into three subsets of our data: All groups encountered ( left ), groups containing known bubble net feeders ( center ), and groups containing whales not known to bubble net feed ( right ). - Janie Wray (457395); Eric Keen (11014169); Éadin N. O’Mahony (11014172) (2021)
Grey dots represent the Association Rate calculated for each time lag (in days) tested. Black line is the running mean of LIR (window = 10 days, first point forced to the τ = 1, last point forced to the final τ ). Blue line and shaded area represent the median and 95% confidence interval (2.5% and 97.5% quantiles), respectively, of the randomized null model (n = 100). Lags at which the running mean rises above the shaded area indicate significantly stable dyadic associations. The orange line on the left plot (‘All groups’) represents the best-fitting SOCPROG model of LAR (see S7 Table in S1 File ).